Pemanfaatan Model Pentahelix Sebagai Bentuk Kolaborasi dalam Meningkatkan Inklusi Keuangan Melalui Peer-To-Peer Lending Syariah di Indonesia - Hibrizi, Emil (Educationist: Journal of Educational and Cultural Studies, 2023)
One of the causes of social inequality in society is the low accessibility of the community to financial services from financial institutions or unbankable. This can hinder the community in carrying out economic activities, especially in obtaining access to micro-business credit. One of the reasons for the higher level of unbankable population among middle to lower class society is the difficulty in obtaining financial access, especially from commercial banks that have selective requirements in providing loans. To overcome this problem, a breakthrough is needed by applying the Pentahelix model through the establishment of Sharia Peer-to-Peer Lending as a form of real collaboration and a step towards increasing financial inclusion, especially for middle to lower class society. The use of the Pentahelix model in the Sharia Peer-to-Peer Lending industry is expected to accelerate the process of increasing financial inclusion for middle to lower class society in Indonesia through strong collaboration between government, society, academics, entrepreneurs, and media, each of which has its own role.